2009
DOI: 10.2337/dc08-1881
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Control of Blood Pressure and Incident Diabetes

Abstract: OBJECTIVE -Incidence of type 2 diabetes might be associated with preexisting hypertension. There is no information on whether incident diabetes is predicted by blood pressure control. We evaluated the hazard of diabetes in relation to blood pressure control in treated hypertensive patients.RESEARCH DESIGN AND METHODS -Nondiabetic, otherwise healthy, hypertensive patients (N ϭ 1,754, mean Ϯ SD age 52 Ϯ 11 years, 43% women) participated in a network over 3.4 Ϯ 1 years of follow-up. Blood pressure was considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 27 publications
6
54
0
4
Order By: Relevance
“…4,5 Diabetes also worsens survival in patients who develop clinical CVD. 6 We have previously demonstrated that uncontrolled blood pressure (BP) is associated with a two-fold increased risk of incident diabetes in treated hypertensive subjects, 7 extending previous observations indicating that incident diabetes is more frequent in hypertensive than in normotensive subjects, 8 and that combinations of hypertension, obesity, and abnormal lipid profile, which often coexist with diabetes, are associated with preclinical cardiovascular abnormalities. 1,9,10 Interestingly, clusters of metabolic abnormalities and the presence of LVH are also reported to increase the probability of uncontrolled hypertension.…”
Section: Introductionsupporting
confidence: 48%
See 3 more Smart Citations
“…4,5 Diabetes also worsens survival in patients who develop clinical CVD. 6 We have previously demonstrated that uncontrolled blood pressure (BP) is associated with a two-fold increased risk of incident diabetes in treated hypertensive subjects, 7 extending previous observations indicating that incident diabetes is more frequent in hypertensive than in normotensive subjects, 8 and that combinations of hypertension, obesity, and abnormal lipid profile, which often coexist with diabetes, are associated with preclinical cardiovascular abnormalities. 1,9,10 Interestingly, clusters of metabolic abnormalities and the presence of LVH are also reported to increase the probability of uncontrolled hypertension.…”
Section: Introductionsupporting
confidence: 48%
“…These findings are eventually reinforced by the evidence that poor therapeutic control of BP further increases the risk of incident diabetes in hypertensive subjects. 7 Considering this evidence, it is not surprising that we found that conditions of preclinical CVD, such as LVH and CA, precede and predict incident diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Следует пом-нить о том, что само по себе наличие АГ ассоциировано с более высоким риском развития сахарного диабета в течение жизни. О том, что недостаточный контроль АД на фоне антигипертензивной терапии может быть независимым фактором риска развития сахарного диабета, показало исследование Izzo R et al [25]. При наблюдении за 1 754 пациентами без сахарного диа-бета (средний возраст 52 года, 43% женщины), по-лучавшими антигипертензивную терапию, в течение 3,4 лет у 109 развился сахарный диабет.…”
Section: рациональная фармакотерапия в кардиологии 2010;6(4)unclassified